Unconscious errors enhance prefrontal-occipital oscillatory synchrony - Cohen, Michael X.; Van Gaal, Simon; Ridderinkhof, K. Richard; Lamme, Victor (Frontiers in Human Neuroscience, 2009)
The medial prefrontal cortex (MFC) is critical for our ability to learn from previous mistakes. Here we provide evidence that neurophysiological oscillatory long-range synchrony is a mechanism of post-error adaptation that occurs even without conscious awareness of the error. During a visually signaled Go/No-Go task in which half of the No-Go cues were masked and thus not consciously perceived, response errors enhanced tonic (i.e., over 1-2 seconds) oscillatory synchrony between MFC and occipital cortex leading up to and during the subsequent trial. Spectral Granger causality analyses demonstrated that MFC >  occipital cortex directional synchrony was enhanced during trials following both conscious and unconscious errors, whereas transient stimulus-induced occipital >  MFC directional synchrony was independent of errors in the previous trial. Further, the strength of pre-trial MFC-occipital synchrony predicted individual differences in task performance. Together, these findings suggest that synchronous neurophysiological oscillations are a plausible mechanism of MFC-driven cognitive control that is independent of conscious awareness.